Some reflections on the concept application of essence over form in leasing operations in the lessee and lessor before and after IFRS 16 - Jorge Katsumi Niyama; Paulo César de Melo Mendes (Revista Ambiente Contábil)
Purpose: The present theoretical essay aims to assess the impacts of normative changes on the topic through a comparative study of the standards, emphasizing the approach related to “substance over form”.